'Posing for all the characters in the book': the multimodal processes of production in Alison Bechdel's relational autobiography Are You My Mother?. Issue 3 (2nd July 2016) - Rüggemeier, Anne
Abstract : During the production process of her graphic novels, Alison Bechdel poses for all the characters (including her own former self), then makes a photo via a self-timer, and finally reproduces this photography via her hand drawing. As a consequence, her comics not only combine words and (drawn) pictures, but they also materialise various modes of experience: first, Bechdel performs a scene from the past with her own body, then she takes a photograph of that performance, then she reproduces the photograph in the mode of a handmade drawing, then that drawing is put into print via technical reproduction. Especially in the context of graphic auto/biography, this production process triggers certain questions concerning authenticity and self-staging. However, Bechdel not only performs her former self, but also re-embodies other people's past experiences, which becomes particularly clear when she starts to learn her late father's handwriting to be able to reproduce his letters to her mother. Against this background, the current article argues that Bechdel uses her own body as a medium of experience and interconnection that allows her to transgress the limited focalisation that the autobiographer is usually bound to, thereby working towards an intersubjective representation of the past.